2021
DOI: 10.1111/jopy.12677
|View full text |Cite
|
Sign up to set email alerts
|

Self‐defining memories—Narrative features in relation to adaptive and maladaptive personality traits (replication and extension of Blagov & Singer, 2004)

Abstract: Objective Self‐defining memories (SDMs) are units of life‐story analysis, whose features resemble elements from narrative identity’s factorial structure. To bridge narrative‐identity and personality‐trait domains, we conducted a replication and extension of prior research. Method We linked four SDM features – affect, specificity, meaning making, and content – to the Big Three trait domains of personality and psychopathology in a small sample that was well‐powered for multilevel modeling (133 participants, 1330… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…Blagov et al (2016;2022) described the collection of these data (self-reported traits and researcher-coded SDM features) and described the participants, who included 120 U.S. undergraduates (77% women, M age = 19.7, SD = 1.32; see also Supplementary Materials, Table S1). Blagov et al (2022) discussed the substantial power provided by 10 SDMs per 120 participants for multilevel modeling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blagov et al (2016;2022) described the collection of these data (self-reported traits and researcher-coded SDM features) and described the participants, who included 120 U.S. undergraduates (77% women, M age = 19.7, SD = 1.32; see also Supplementary Materials, Table S1). Blagov et al (2022) discussed the substantial power provided by 10 SDMs per 120 participants for multilevel modeling.…”
Section: Methodsmentioning
confidence: 99%
“…Diverse narrative variables interrelate (McLean et al, 2020) and may predict well-being incrementally over other constructs (Adler et al, 2016). For example, replicable research links psychological adjustment to greater positive emotions, memory specificity and meaning making, and to lower negative emotions and thematic downturns in self-defining memories (SDMs; Blagov et al, 2022). Conversely, personal narratives with limited emotion, specificity, and meaning lack coherence and suggest unhealthy identity development (Adler et al, 2012).…”
Section: Expression and Detection Of Triarchic Psychopathy Traits In ...mentioning
confidence: 99%
“…Table 1 shows that only three previous studies explored contamination or redemption in healthy adults’ SDMs (Blagov et al, 2022; Cuervo-Lombard et al, 2021; Lardi et al, 2010), that is an explicit transformation, in the narratives, from a positive to a negative state or the opposite evolution (McAdams et al, 2001). They showed that contamination sequences were high in college students (Blagov et al, 2022; Lardi et al, 2010) but very low in midlife and later life (Cuervo-Lombard et al, 2021). Two of these studies reported that the frequency of redemptive SDMs seemed to decrease with age: it was relatively high in emerging adults (Lardi et al, 2010), lower in middle-aged adults, and even lower in older adults (Cuervo-Lombard et al, 2021).…”
Section: Main Dimensions Of Sdmsmentioning
confidence: 99%
“…Two of these studies reported that the frequency of redemptive SDMs seemed to decrease with age: it was relatively high in emerging adults (Lardi et al, 2010), lower in middle-aged adults, and even lower in older adults (Cuervo-Lombard et al, 2021). In contrast, Blagov et al (2022) found that redemptive sequences in memories were low in young participants.…”
Section: Contamination and Redemptionmentioning
confidence: 99%
See 1 more Smart Citation